Titanium surface interacting with blood clot enhanced migration and osteogenic differentiation of bone marrow mesenchymal stem cells - Li, Jia; Zhao, Juan; Xu, Yangbo; Xu, Antian; He, Fuming (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Blood clot formation is the initial phase upon implantation, and the feature of blood clot orchestrates the following complement system activation, coagulation cascade, and bone marrow mesenchymal stromal cells (BMSCs) recruitment. This study aimed to investigate the effect of implant surface on blood-material interactions and subsequent BMSC cellular behaviors. Methods: This study was established to imitate the physiological process of implantation in vivo and in vitro. Whole blood was incubated with polished titanium (PT) surfaces and sandblasted and double acid-etching (SLA) surfaces for 10 min or 2 h, then seeded with BMSCs. The adhesion, proliferation, migration, and differentiation of cells were studied at specific time points. Titanium implants were implanted into the tibia in vivo and were screwed out after implantation. The activation of the coagulation cascade, platelets, complement system, and clot networks were assessed and further quantitatively analyzed. Results: Compared with the PT surface, the SLA surface induced the earlier and stronger blood coagulation cascade and formed a more stratified clots network with fibrinogen, platelets, and CD14 positive cell. The adhesion, proliferation, and migration of BMSCs were enhanced by pre-incubated surfaces. The higher levels of the osteogenic-related genes, ALP activity, and calcium nodule formation were showed on SLA surfaces with blood incubation. Conclusion: SLA titanium surfaces play a role in influencing the formation of blood clots and coordinating surface-blood interactions and cell biological processes. These findings provide the idea of modifying the blood clots formed on the implant surface by biomaterials modification and thus has implications for the development of better osteogenic biomaterials.